The International Protection of Workmen - Miller, A. C. (Quarterly Journal of Economics, 1889)
Journal Article The International Protection of Workmen Get access A. C. Miller A. C. Miller Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 3, Issue 4, July 1889, Pages 481–496, https://doi.org/10.2307/1879644 Published: 01 July 1889